the Effectiveness of two Counseling Programs in Reducing the Symptoms of Social Phobia Disorder among Freshmen Students at Yarmouk University - Gazo, Ahmad; Samour, Qassim (Jordan Journal of Educational Sciences, 2016)
This study aimed to measure the effectiveness of two counseling programs in reducing the symptoms of social phobia disorder among freshmen students at Yarmouk University. Population of the study consisted of all enrolled freshmen at the first semester of the academic year 2013\2014 students totaling (9510) freshmen (5346 female and 4164 male). To achieve the objective of the study, the researcher used Lipbowitz Social Phobia Scale consisting of (18) items. Based on the means scores of a convenient sample (523) (318 females and 205 males) selected from the population and their willingness to participate in the study, the final sample of the study consisting of (36) students (22 female and 14 male) was selected and randomly assigned into three study groups, each consisting of (12) students. The first study group was given a social skills training program, the second experimental group was given a gradual sensitivity reduction training program, while the third program represented the control group. Results of the study indicated that both training programs (social skills training program and gradual sensitivity reduction) were more effective at significance level (α =0, 05) in reducing social phobia among the sampled students. No significant differences were found in the effectiveness of both training programs due to the interaction between gender and experimental group. Three weeks after the programs follow up data indicated that the sampled students in the experimental group retained their gains due to the participation in the counseling programs